1994
DOI: 10.1007/bf02167900
|View full text |Cite
|
Sign up to set email alerts
|

The relations between emotional understanding, intellectual functioning, and disruptive behavior problems in elementary-school-aged children

Abstract: This study examined individual differences in children's emotional understanding and behavioral adjustment. Participants included 220 first- and second-grade children (75% regular education, 25% special education) who were individually interviewed using the Kusche Affective Interview--Revised. Dependent measures of emotional understanding and experience included the ability to provide personal examples of 10 different emotions and the cues used for recognition of five emotions in oneself and other persons. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 12 publications
6
93
1
3
Order By: Relevance
“…It is also uncertain whether the evidence suggests limited emotion understanding or a reluctance to discuss emotions (or some combination) among children experiencing significant psychological problems (cf. Cook et al, 1994). Considering also the paucity of work in general, conclusions discussed are tentative and await additional work.…”
Section: Emotion Understanding: Psychopathological Populationsmentioning
confidence: 92%
See 1 more Smart Citation
“…It is also uncertain whether the evidence suggests limited emotion understanding or a reluctance to discuss emotions (or some combination) among children experiencing significant psychological problems (cf. Cook et al, 1994). Considering also the paucity of work in general, conclusions discussed are tentative and await additional work.…”
Section: Emotion Understanding: Psychopathological Populationsmentioning
confidence: 92%
“…For example, abused and maltreated children exhibit deficits in the recognition of face expressions of emotion (e.g., Camras, Grow, & Ribordy, 1983;Camras & Rappaport, 1993;Camras et al, 1990;Camras et al, 1988). Maltreated children, children at risk for disruptive behavior disorders, and ''hardto-manage'' preschoolers demonstrated poorly developed understandings of the causes of emotion, for example, by providing fewer appropriate examples of triggers or cues for emotion (e.g., Camras, Sachs-Alter, & Ribordy, 1996;Cook, Greenberg, & Kusche, 1994;Greenberg et al, 1995;Rogosch, Cicchetti, & Aber, 1995;Shipman & Zeman, 1999). In one study of maltreated children, not only was the emotion understanding of the maltreated children lower than nonmaltreated youth but also the mothers of maltreated children were less likely to discuss emotional topics in a mother-child interactions task (Shipman & Zeman, 1999), recalling the important scaffolding role of parents in emotional development.…”
Section: Emotion Understanding: Psychopathological Populationsmentioning
confidence: 99%
“…Several studies of emotion processes and aggressive behavior may be relevant to the SIP model. Concerning encoding and interpretation, studies of emotion attribution in aggressive boys have shown that aggressive behavior problems are related to atypical labeling of emotion expressions (Cook, Greenberg, & Kusche, 1994;Izard, Schultz, & Ackerman, 1997). Whether this involves systematic attribution of specific emotions (for example, to consider a sad facial expression angry) and how these attributions relate to the intent attributions studied in the SIP framework is, however, unclear.…”
mentioning
confidence: 99%
“…Für Kinder mit externalisierenden Problematiken (Aggression, ADHS) konnten konsistent schlechtere Leistungen im Emotionserkennen (Nowicki u. Duke, 1994;Cadesky, Mota, Schachar, 2000;Walker u. Leister, 1994) und im Verstehen von Emotionsursachen nachgewiesen werden (Hughes, Dunn, White, 1998;Cook, Greenberg, Kusche, 1994 (Fonzi et al, 1999;Nowicki u. Duke, 1994;Cadesky, Mota, Schachar, 2000;Walker u. Leister, 1994;Woods et al, 2009;Baumgartner u. Alsaker, 2008). Bei viktimisierten Kindern wären Probleme im Verständnis von Emotionsursachen und in der Modulation/Enkodierung des Emotionsausdrucks (Regulation und Verbergen) kongruent mit den Befunden von Mahady et al (2000), Cowie und Berdonini (2002), Hughes, Dunn und White (1998) und Southam-Gerow und Kendall (2000.…”
Section: Emotionsverständnis Von Kindern Mit Verhaltensproblemenunclassified